006 Healthcare computing development: GOSH project experience working with UCL computer science (CS) industry exchange network (IXN). (December 2018) - Mohamedally, D; Fu, Y; Conner, S; Priestman, W; Sridharan, S; Hughes, G; Winstanley, T; Sebire, NJ
Abstract : Background: There is an urgent need for the UK healthcare sector to increase clinical informaticians and healthcare computing expertise and workforce (Wachter report/Topol review) but no national plan for achieving this goal. Aim: We describe the initial experience with the UCL GOSH Industry Exchange Network (IXN) programme in healthcare. Methods: The IXN programme allocates UCL Computer Science (CS) students to 'real-world' projects at Great Ormond Street Hospital (GOSH) supported by industry/corporate partners (Microsoft/NTT Data). Student projects receive input from clinical experts ('clients'), CS academic supervisors (academia) and corporate/technology companies (partners) to address the healthcare issues. Results: The initial programme included 33 undergraduate CS students allocated in teams of three to 11 GOSH healthcare projects on subjects including: growth charts, augmented reality gamification, content delivery systems, patient safety, staff training and patient instruction mobile apps, medical drawing tools, secure communication devices and interactive booking systems among others. All projects resulted in satisfactory outcomes in terms of GOSH deliverables and student project marks. Around half of the projects demonstrated a successful proof of principle such that ongoing development is planned or underway and three projects are being translated directly to operational deployment following minor additional development effort. Conclusion: The healthcare, academic and industry IXN offers the unique opportunity to provide 'real world' project experience for CS students and a platform for the NHS to significantly accelerate early phase digital development. This highly effective model should be considered an exemplar for expanding the new area of healthcare computing and clinical informatics.